A Study on Retail Store Service Quality Dimensions in Select Retail Stores of Chennai City - Tamilarasan, R. (Indian Journal of Marketing, 2007)
Retailing is a constantly changing industry as ultimate customers’ change themselves. In a way, Retailing is a fascinating world. One industry, which has made a phenomenal impact on our daily lives, is retail. It touches our lives, as end consumers. Retailing has been in our blood-as a shopkeeper or as a shopper.India is a nation of around 12million retailers. The total value of the Indian retail sector is estimated around Rs.9,00,000 crore, of which the organized sector accounts for 2% percent. Retail business in India, contributes 10-11% of the GDP and employs 7% of the workforce in the country.India has the largest retail density in the world with 12million retail outlets for a population of over a 100million, though as much as 90% of these are smaller than 500sq.ft.in area. This means that in India, the per capita retailing space is about 2sq.ft, compared to 16sq.ft, in the US. On the other hand, organized retailing in India is relatively a new phenomenon which is witnessing a high growth. Retail is swinging across India; Retailing represents a huge business opportunity as it is in a transition phase as well as favorable deliberations in favour of allowing foreign direct investment in retail sector. Hence, it is likely to open up the door for the entry of global retail giants, like Walmart. In the light of the above, this research has been undertaken to assess the customer service and the retail store service quality dimensions as prevalent in the leading stores of Chennai city. Moreover, customers often look at something more than the assortment of goods, in this context, the importance of a well-thought out customer service strategy becomes critical. In other words, the total customer service or the total experience that a customer gets in the store can stay unique. Very often, in retail, it is not what you sell that counts, but how you sell it does matter. Hence, this research focuses on the customer service being provided by the leading stores is brought under the present study.